PENGARUH STRUKTUR KEPEMILIKAN TERKONSENTRASI, KEPEMILIKAN ASING, DAN UKURAN DEWAN DIREKSI TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN INDEKS LQ 45 YANG TERCATAT DI BURSA EFEK INDONESIA - Niazi Nizami; A. Sakir (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to analyze the effect of the structure of concentrated ownership, foreign ownership, and the size of the board of directors on firm performance. Concentrated ownership is assessed using a dummy variable, which is giving a score of 1 for companies that have concentrated ownership and a score of 0 for companies that have spread share ownership, sponsored ownership by adding up the intended shares and the number of shares exchanged, the size of the directors existing with the number of the entire board directors, as well as the firm's performance obtained by the value of Return on Assets. The sampling technique uses purposive sampling technique. Data analysis technique on the LQ 45 company index published on the Indonesia Stock Exchange for period 2013-2018. Obtained from the results of a significant positive significant effect on firm performance. Foreign ownership increases a significant negative on firm performance. The size of the board of directors has a significant positive effect on firm performance